MUC1 Specific Immune Responses Enhanced by Coadministration of Liposomal DDA/MPLA and Lipoglycopeptide - Du, Jing-Jing; Zhou, Shi-Hao; Cheng, Zi-Ru; Xu, Wen-Bo; Zhang, Ru-Yan; Wang, Long-Sheng; Guo, Jun (Frontiers in Chemistry, 2022)
Mucin 1 (MUC1), a well-known tumor-associated antigen and attractive target for tumor immunotherapy, is overexpressed in most human epithelial adenomas with aberrant glycosylation. However, its low immunogenicity impedes the development of MUC1-targeted antitumor vaccines. In this study, we investigated three liposomal adjuvant systems containing toll-like receptor 4 (TLR4) agonist monophosphoryl lipid A (MPLA) and auxiliary lipids of different charges: cationic lipid dimethyldioctadecylammonium (DDA), neutral lipid distearoylglycerophosphocholine (DSPC) or anionic lipid dioleoylphosphatidylglycerol (DOPG), respectively. ELISA assay evidenced that the positively charged DDA/MPLA liposomes are potent immune activators, which induced remarkable levels of anti-MUC1 antibodies and exhibited robust Th1-biased immune responses. Importantly, the antibodies induced by DDA/MPLA liposomes efficiently recognized and killed MUC1-positive tumor cells through complement-mediated cytotoxicity. In addition, antibody titers in mice immunized with P2-MUC1 vaccine were significantly higher than those from mice immunized with P1-MUC1 or MUC1 vaccine, which indicated that the lipid conjugated on MUC1 antigen also played important role for immunomodulation. This study suggested that the liposomal DDA/MPLA with lipid-MUC1 is a promising antitumor vaccine, which can be used for the immunotherapy of various epithelial carcinomas represented by breast cancer.